2017
DOI: 10.3126/ijasbt.v5i2.17616
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Production in Nepal: Characteristics, Productivity and Constraints

Abstract: Poultry farming is integral part of agriculture in Nepal. The objective of this research was to analyze the prevailing production constraints, characterization of poultry farming and its economic analysis using questionnaire-based survey and on-site investigation. 180 farms were selected from 3 major districts. Garrett's ranking technique was used to analyze the constraints. Highly significant difference (P<0.01) in size of poultry farm was found. We found significant difference in feeding, housing and drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In many countries including Nepal, there is excessive use of antibiotics in poultry industries. Studies have reported that antibiotics have been used in chicken broilers as growth promoter and disease preventive measures [ 6 , 7 ]. However, utilization of antimicrobials in food producing animals have created several adverse effects, such as changes in intestinal micro flora, presence of residual antibiotics in food products, impact on public environment, and emergence of antimicrobial resistance in microorganisms [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries including Nepal, there is excessive use of antibiotics in poultry industries. Studies have reported that antibiotics have been used in chicken broilers as growth promoter and disease preventive measures [ 6 , 7 ]. However, utilization of antimicrobials in food producing animals have created several adverse effects, such as changes in intestinal micro flora, presence of residual antibiotics in food products, impact on public environment, and emergence of antimicrobial resistance in microorganisms [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poultry industries are emerging rapidly in the developing countries like Nepal. Chitwan, Kathmandu, and Kaski districts are the major areas of poultry farms in Nepal [ 6 ]. Chitwan district solely produces 68% and 10% of total eggs and chicken meats, respectively in the country [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamentals of successful management of poultry projects is the control of the way and quantity of feed provided; otherwise large amount of feed will be lost. It seems that because of traditional production methods, producers suffer from loss of large amount of feed, and thus ranked it the fifth most severe among production constraints, which is in line with the findings of Osti et al, (2017). Many diseases attack poultry, which are considered an important cause of huge economic loss for poultry producers.…”
Section: Discussionmentioning
confidence: 57%
“…It happen due to a combination of improper feeding practices, ignorance of management needs, poor distribution of vaccines, presence of diseases, and bad weather condition ( Addis et al,2014;Islam et al, 2014) . High mortality rate is a common problem in most countries including Iraq (Anang et al, 2013;Food and Agriculture Organization, 2014;Sharif et al,2014;Akbay and Azeez, 2016;Kraidi et al,2016;Yemane et al,2016;Mbuza et al,2017;Osti et al, 2017). Poultry producers in Babylon province suffer from high mortality rate and thus ranked it as third most important.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken contribute a significant proportion to the national economy as well the national food and nutritional status of Nepal (Sharma et al, 2008;Osti et al, 2017). The value of chicken meat is increasing everyday as it is considered safe for individuals with various health and metabolic complications.…”
Section: Introductionmentioning
confidence: 99%